Increasing Compulsory Citizenship Behavior and Workload: Does Impression Management Matter? - Liu, Fang; Chow, Irene H.; Huang, Man (Frontiers in Psychology, 2019)
The present study focuses on the dark side of impression management (IM) and proposes that IM tactics (ingratiation, exemplification, and their interaction) positively affect workload through the mechanism of compulsory citizenship behavior. We tested our hypotheses with data from 298 employees in China. Results revealed that ingratiation, exemplification, and their interaction, were positively related to workload, and compulsory citizenship behavior played a mediating role in all these relationships. We discussed the theoretical and practical implications of this study.